Industrial energy conservation, rebound effects and public policy - van den Bergh, Jeroen C.J.M. (UNIDO AT, 2011)
Outlines the problem of energy rebound and defines its relevance for firm management and the design of public and governmental policies aimed at stimulating energy conservation and improvements in energy efficiency.